Capital-Markets Crisis and Economic Collapse in Emerging Markets: An Informational-Frictions Approach - Calvo, Guillermo A; Mendoza, Enrique G (American Economic Review, 2000)
Capital-Markets Crises and Economic Collapse in Emerging Markets: An Informational-Frictions Approach by Guillermo A. Calvo and Enrique G. Mendoza. Published in volume 90, issue 2, pages 59-64 of American Economic Review, May 2000